Immunological Profile of Postoperative Colorectal Cancer Patients: Evaluation of TNF-α, IL-12, , IL-4, and IFN-γ - Murtada Wafi Beden (Academia Open, 2026)
General Background: Colorectal cancer is a prevalent malignancy associated with complex immune responses that persist after surgical intervention. Specific Background: Cytokines such as TNF-α, IFN-γ, IL-12, and IL-4 regulate tumor immunity and reflect postoperative immunological status. Knowledge Gap: Limited data exist regarding the cytokine profile and immune balance in postoperative colorectal cancer patients, particularly in relation to inflammatory and regulatory responses. Aims: This study aimed to evaluate serum levels of TNF-α, IFN-γ, IL-12, and IL-4 in postoperative colorectal cancer patients and characterize their immunological profile. Results: In a cross-sectional study of 67 patients, mean cytokine levels were TNF-α (137.64 ± 38.15 pg/mL), IFN-γ (30.47 ± 5.75 pg/mL), IL-12 (23.76 ± 12.07 pg/mL), and IL-4 (5.21 ± 2.07 pg/mL). Elevated TNF-α and IFN-γ indicated persistent pro-inflammatory and cell-mediated immune activation, while lower IL-4 levels suggested limited anti-inflammatory regulation. Significant correlations were observed between postoperative duration and TNF-α, IL-12, and IL-4, as well as a negative correlation between IL-12 and IFN-γ. Novelty: This study provides a defined cytokine pattern demonstrating Th1-dominant immune response in postoperative colorectal cancer patients. Implications: Cytokine profiling may serve as a valuable approach for immune monitoring and understanding postoperative immune dysregulation in colorectal cancer management. Highlights:• Elevated pro-inflammatory mediators indicate sustained immune activation after surgery• Reduced anti-inflammatory response reflects imbalance in immune regulation• Cytokine correlations reveal interaction between postoperative duration and immune markers Keywords: Colorectal Cancer, Cytokine Profile, TNF-Alpha, Interferon Gamma, Interleukin-12